Exploring Leadership approaches of Women in Climate Justice: Pathways to Impact and Empowerment - Ahmad, Husna (International Journal of Civilizations Studies & Tolerance Sciences, 2024)
This paper will examine the role of women in promoting peace through leadership in the climate justice space; through building an inclusive climate movement to tackle the triple planetary crisis facing the globe. Studies reflect that marginalised populations are disproportionately affected by climate change and environmental degradation, particularly indigenous communities and women, despite contributing the least to climate catastrophe. Women are among the 32.6 million climate migrants and refugees each year, who are in turn, at risk of experiencing gender-based violence. Standing at the frontlines of the triple planetary crisis, women are ideally placed to take up leadership roles within efforts toward achieving climate justice and a sustainable future. Women serve as primary caregivers, often responsible for providing food and water security, sustaining families and households in climate-affected regions. They are the first guardians and caretakers of our youth, possessing the necessary emotional depth, compassion, and maternal instinct to promote the values underpinning climate justice, which at its core, advocate for the sustenance of Mother Earth through an empathetic lens. Women, at the helm of community development and holistic wellbeing, are integral to building peaceful global communities through forming compassionate networks of changemakers, leaders and entrepreneurs adopting sustainable livelihood approaches. Following a conference on “Women, Religion and Climate Change, working together to move faster on climate change” which took place at Wilton Park in the UK in September 2023, an official report of findings and recommendations was produced, highlighting the real-life experiences, opportunities, and challenges within this arena. This report will serve as a key case study for this paper, drawing on discussions and focus groups among the diverse multi-lateral participants, influencers, and faith leaders present at this event. This paper will consider emerging approaches related to female leadership including the capability approach, the whole community approach, and the Islamic concept of Maslaha [Maslaha is an Arabic word, which means public interest]. These approaches also promote peaceful and sustainable societies and communities.